The COVID-19 pandemic: challenges in providing supportive care to those with cardiovascular disease in a time of plague - Hill, Loreena Michelle; Lambrinou, Ekaterini; Moser, Debra K.; Beattie, James M. (My University, 2021)
Purpose of review COVID-19 has permeated the very essence of human existence and society and disrupted healthcare systems. The attrition stemming from this highly contagious disease particularly affects those rendered vulnerable by age and infirmity, including those with underlying cardiovascular disease. This article critically reviews how best to integrate supportive care into the management of those affected. Recent findings Numerous studies have described the pathophysiology of COVID-19, including that specifically arising in those with cardiovascular disease. Potential treatment strategies have emerged but there is limited guidance on the provision of palliative care. A framework for implementation of this service needs to be developed, perhaps involving the training of non-specialists to deliver primary palliative care in the community, bolstered by the use of telemedicine. The appropriate use of limited clinical resources has engendered many challenging discussions and complex ethical decisions. Prospective implementation of future policies requires the incorporation of measures to assuage moral distress, burnout and compassion fatigue in healthcare staff who are psychologically and physically exhausted. Summary Further research based on patient-centred decision making and advance care planning is required to ensure the supportive needs of COVID-19 patients with cardiovascular disease are adequately met. This research should focus on interventions applicable to daily healthcare practice and include strategies to safeguard staff well-being.
Keywords: Advance Care Planning; Burnout; Cardiovascular Diseases; Communication; Compassion Fatigue; COVID-19; Cultural Competency; Decision Making; Palliative Care; Pandemics; Patient Participation; SARS-CoV-2; Telemedicine